The effect of an educational intervention based on the theory of planned behavior on the prevention of knee osteoarthritis in women - Zhila Fereidouni; Mina Bahmandoost; Pooyan Afzali Harsini; Ali Khani Jeihooni (Scientific Reports)
Abstract Knee osteoarthritis offers significant opportunities for prevention and the mitigation of its severity and associated symptoms through lifestyle modifications. This study aimed to investigate the efficacy of an educational intervention based on the Theory of Planned Behavior (TPB) in promoting preventive behaviors against knee osteoarthritis among women aged over 40 years residing in Fars, Iran. This research utilized a quasi-experimental design. The study population comprised 100 women over the age of 40 who were registered at health centers in Fasa, Iran. Data were collected using a questionnaire based on the Theory of Planned Behavior (TPB). The intervention was implemented through eight educational sessions specifically designed to promote TPB-informed preventive behaviors against knee osteoarthritis. The findings revealed statistically significant differences between the experimental and control groups regarding their scores on attitude, subjective norms, perceived behavioral control, intention, and behavior, both before and after the intervention. At 3 months post-intervention, the experimental group demonstrated significant improvements in all measured constructs, while the control group showed no substantial changes. This study demonstrates that implementing structured educational interventions grounded in behavioral theory, specifically the Theory of Planned Behavior (TPB), can effectively promote preventive behaviors against knee osteoarthritis, thereby potentially reducing its associated morbidity.